Diáspora e velhice dos imigrantes Hakka: a memória da alma - Ling, Chiou Ruey (2008)
To present a work about the Chinese immigration there is without a doubt an interest in the study of the subjects put by the immigration and numerous works in the anthropology areas and sociology can be found. No there is, however, a reflection or more study on the etnias that you/they interest us. In the study, Diaspora and Old age of the Immigrant Hakka: the memory of the soul, leaves of the idea of the immigration, the old age, the process of adaptation of Hakka, taking as reference the community from São Paulo. We considered, on a side, short time of the arrival of these groups in Brazil and his concern in maintaining alive the origin traditions and on the other hand, the fact of, contradictory be dipped in a western society in process of fast changes and radicals. In this scenery it is that they are born and the new generations of universes are socialized Hakka